Hypereosinophilic syndrome associated with idiopathic eosinophilic vasculitis - B. Subhani; B. M. A. C. Yashodara; M. Sivapalan; U. Dissanayake (Asian Journal of Internal Medicine)
Hypereosinophilic syndrome (HES) is a complex heterogenous syndrome associated with hypereosinophilia and end organ involvement. A 46-year-old woman presented with swelling of the upper and lower limbs, neck and face, with shortness of breath. On examination there was evidence of dermal oedema with an urticarial rash. Investigations revealed high absolute eosinophil count, evidence of cutaneous vasculitis and increased bone marrow eosinophilic precursors. There was no other end-organ involvement. There was a recurrence of symptoms despite an initial course of glucocorticoids. However, she later responded to long-term imatinib. This case highlights the importance of considering HES with idiopathic cutaneous vasculitis even in the absence of significant systemic involvement.